KINERJA BADAN AMIL ZAKAT PROVINSI SULAWESI TENGAH (Mengumpul dan Mendistribusikan Zakat) - Bahdar Bahdar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
This research was conducted at Badan Amil Zakat National Central Sulawesi Province (BAZNAS) to know the collection of zakat and infak fund and its distribution. In this study data collection using survey sample method that only records a small part of the object of research and for each element is investigated in depth which operations. Through this research it is known that: National Amil Zakat Agency of Central Sulawesi Province collects zakat funds limited to Civil Servants and Officials in Provinsi environment. Excluding Civil Servants and Officials in Town and Regency in Parovinsi Central Sulawesi. Also excluding entrepreneurs and the general public. Zakat issued by Civil Servants and Officials is Zakah on Income, not zakat mal or zakat treasure. So that collected by the Amil Body is zakat based on the amount of salary and other income for one year. So the treasures of vehicles, gardens, houses, jewelry and others are not subject to zakat.Besarnya earnings collected 2.5 percent equivalent to 85 grams of gold. Zakat is collected through the collecting unit of zakat (UPZ) in each institution. DPD and SKPD in Central Sulawesi Province. Zakat is channeled to mustahik with the consideration of fulfilling basic necessities mustahik